أساليب المواجهة لدى المراهقين المعاقين عقليا القابلين للتعلم والعاديين : دراسة مقارنة - علي، أحمد فتحي (رابطة التربويين العرب, 2012)
هدف البحث إلى دراسة مقارنة بين أساليب المواجهة لدى المراهقين المعاقين عقلياً (القابلين للتعلم) والعاديين، وتكونت العينة من (70) طالباً وطالبة؛ عبارة عن (35) من المراهقين المعاقين عقلياً، و(35) من المراهقين العاديين من الجنسين، وتراوحت أعمارهم الزمنية بين (14-19) سنة بمتوسط (16.53) وانحراف معياري (1.72) سنة. واستخدم الباحث استمارة بيانات الطلاب المعاقين عقلياً (القابلين للتعلم) والعاديين، ومقياس أساليب المواجهة إعداد (Carver, 1997) وتعديل الباحث. أشارت النتائج إلى وجود فروق ذات دلالة إحصائية في مجال أساليب المواجهة الفعالة في اتجاه المراهقين العاديين والذكور عند مستوى (0.01) ودلت على وجود فروق في أسلوب التماس العون في الجنس فقط عند مستوى (0.05). وأخيراً فلم توجد بينهما فروق دالة في مجال الأساليب السلبية. وقد قام الباحث بتفسير النتائج وفق التراث النظري والدراسات السابقة. This research aims to study the comparison between the methods of confrontation among adolescents with intellectual disabilities (who are the know), and ordinary, and formed the sample of (70) students; by (35) each of the sexes, between the ages of (14-19) year average (16.53) and a standard deviation (1.72) years. The researcher used data form the mentally disabled students and ordinary, and the measure of the preparation methods of confrontation (Carver, 1997) and modify the researcher. The results indicated the presence of statistically significant differences in the techniques of effective confrontation in the direction of ordinary teenagers and males at the level of (0.01), and demonstrated the existence of differences in the way to seek help in sex only when the level of (0.05). Finally, there are no significant differences between the two methods in the negative. The researcher interpretation of the results according to the heritage of the theoretical and previous studies.
Keywords: الطلاب المعاقون -- مرحلة المراهقة -- المراهقون -- التخلف العقلى -- تعليم ذوى الاحتيجات الخاصة -- التربية الخاصة -- السياسة التعليمية